AKULTURASI SAINS, TEKNOLOGI DAN BUDAYA UNTUK PENINGKATAN KUALITAS PENDIDIKAN BERBASIS KEARIFAN LOKAL - Suranto, Suranto (Jurnal Florea, 2014)
The values of local knowledge is the basis of great value for nature conservation, development of local products and development of national character. Indigenous development efforts need to be made by all parties and the whole society, so that the direction of development based on their own national identity. This can be exemplified in the national figures are recognized worldwide, while sticking to the philosophy of the nation. Positive impact on improving the quality of education is expected to be achieved as a result of acculturation between science, technology and culture. Pancasila should be a solid foundation for the development of science and technology, Â so that Indonesia become a nation of characterÂ Keyword: acculturation, science, technology, culture